A BRIEF OUTLINE OF THE FORMATION OF TIWA AUTONOMOUS COUNCIL OF ASSAM AND AN ANALYSIS OF ITS SUCCESS OR FAILURE - Saiki Chamsal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In a diverse and multi-ethnic country like India, the emergence of demand for autonomy by smaller ethnic communities is an obvious and natural phenomenon. Assam is one of the states of India where numerous different tribes reside with their distinct culture, history and way of life. Though after independence some special provisions were incorporated in the constitution for the governance of tribal communities to ensure their development, protection of their culture and identity but their social and political aspirations is still not properly addressed. Tiwa or Lalung is one such tribe of Assam which has raised the demand of political autonomy and struggled for long to secure it. Responding to their demand the Government constituted the Tiwa Autonomous Council ensuring self rule in areas where they are dominant. The following paper is a study of the same and an analysis of its success or failure and the way forward.